Symphytognathidae (Araneae), a spider family newly recorded from China - Tong, Yan-Feng; Li, Shu-Qiang (Zootaxa, 2006)
The family Symphytognathidae is reported from China for the first time. A new species of the genus Anapistula Gertsch, 1941, named Anapistula appendix sp. nov., is described and figured. The spider was recorded in a cave in Hainan, the second-largest island in southern China.